2016
DOI: 10.19082/2576
|View full text |Cite
|
Sign up to set email alerts
|

Visual Detection of Enterohemorrhagic Escherichia coli O157:H7 Using Loop-Mediated Isothermal Amplification

Abstract: IntroductionEscherichia coli O157:H7, an important foodborne pathogen, can cause serious renal damage, which can also lead to mortality. Since a rapid and sensitive method is needed to identify this pathogenic agent, we evaluated Loop-Mediated Isothermal Amplification Assay (LAMP) to detect Escherichia coli O157:H7.MethodsWe used six primers that specifically identified the rfbE gene. To examine the sensitivity of the method, different dilutions were subjected to the LAMP reaction. Other bacterial strains also… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
14
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 47 publications
1
14
0
Order By: Relevance
“…Second, as shown by the results in Fig. 3, this assay had higher sensitivity than previously reported LAMP assays (Ranjbar et al 2016;Zhu et al 2009). For example, the LAMP assay targeting the rfbE gene developed by Zhu and colleagues allowed for the positive detection of E. coli O157:H7 with a sensitivity of 26 and 10 CFU/reaction (Zhu et al 2009), whereas the z3276-LAMP-LF detection limit was 1.3 CFU/mL.…”
Section: Discussionmentioning
confidence: 48%
See 1 more Smart Citation
“…Second, as shown by the results in Fig. 3, this assay had higher sensitivity than previously reported LAMP assays (Ranjbar et al 2016;Zhu et al 2009). For example, the LAMP assay targeting the rfbE gene developed by Zhu and colleagues allowed for the positive detection of E. coli O157:H7 with a sensitivity of 26 and 10 CFU/reaction (Zhu et al 2009), whereas the z3276-LAMP-LF detection limit was 1.3 CFU/mL.…”
Section: Discussionmentioning
confidence: 48%
“…Several LAMP methodologies have previously been reported for the detection of E. coli O157:H7 that involve amplifying various target genes, including O-serogroup specific genes (rfbE, wzx, wzy), Shiga toxin genes (stx1 and stx2) (Ranjbar et al 2016;Dong et al2014;Wang et al 2012), and E. coli attaching and effacing gene (eae) (Zhang et al 2013); however, most of these genes are not unique genetic markers for this serotype (Ravan and Amandadi 2015). The inability of these genes to accurately differentiate E. coli O157:H7 from other E. coli serotypes prompted the investigation of novel genetic markers.…”
Section: Discussionmentioning
confidence: 99%
“…Wang and others () also used the EMA–LAMP method for the detection of Vibrio parahaemolyticus in VBNC and dead state. Ranjbar and others () used SYBR Green II with the LAMP method for visual detection of EHEC O157:H7. The positive samples showed green color whereas negative samples were orange in color under UV light.…”
Section: Loop‐mediated Isothermal Amplificationmentioning
confidence: 99%
“…Recently, a LAMP assay was invented which is time-saving, simple to operate, and appropriate in primary clinics or field labs (Notomi et al, 2000). Meanwhile, it can amplify without the process of denaturation and renaturation of nucleic acid under isothermal temperature with 2-3 pairs of primer for more than 10 min and result in 10 9 -10 10 copies of target DNA within 1 hr (Kokkinos, Ziros, Bellou, & Vantarakis, 2014;Ranjbar et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies (Luan & Levin, ; Wu et al, ) have shown that the recovery of foodborne pathogens was significantly improved after bentonite coated activated carbon (BCAC) treatment. Currently, the majority of quality control systems available for the supervision of milk in the food industry use an initial enrichment followed by a detection system such as PCR or LAMP assay (Kokkinos et al, ; Ranjbar et al, ). Such methodology timely precludes the presence of pathogen before the product is shipped.…”
Section: Introductionmentioning
confidence: 99%